Beyond Sectoral Silos: How Community Development Enhances Sector-Based Outcomes-Insights from Tanzania - George Frank Kinyashi (Journal of Sustainable Community Development, 2026)
Sector-based approaches have driven significant investments in infrastructure and service delivery across the Global South. However, evidence from development practice increasingly demonstrates that technical success does not automatically translate into sustained social outcomes. This paper argues that the community development field provides the critical integrative function needed to translate sectoral inputs into meaningful and durable development outcomes. Using a qualitative approach, including document review and practitioner reflective methods, the paper examines how community development enhances relevance, coherence, effectiveness, efficiency, sustainability, and impact of sector-based interventions. It conceptualizes community development professionals as “general social physicians” who diagnose social issues, facilitate participation, and coordinate sectoral expertise to ensure community ownership and long-term benefits. The paper is limited by its over-reliance on secondary sources and expert personal experience. However, it offers a significant novel contribution by presenting the “general social physician” concept as an integrative model depicting the community development field as a coordinating discipline within sector-based development practice. In this way, the paper contributes to international development debates by demonstrating how community development can bridge sectoral silos and strengthen citizen empowerment in low- and middle-income countries.